Pasting Properties of Various Waxy Rice Flours: Effect of α-Amylase Activity, Protein, and Amylopectin - Yuehui Wang; Kuijie Sun; Kai Zheng; Wenchang Zhu; Wenping Ding; Qingyun Lyv; Lei Chen; Guozhen Wang; Kun Zhuang; Xi Chen (Journal of Food Quality)
Waxy rice has a long history of being cultivated and consumed in China. In this study, the effect of different factors including α-amylase activity, protein, and amylopectin structure on the pasting properties of four waxy rice varieties were investigated. Rice flours were divided into four groups (Vietnam indica (VI), Jiangxi indica (JI), Anhui japonica (AJ), and Dongbei japonica (DJ) group) and treated with AgNO3 solution, DL-dithiothreitol (DTT), or protease (n = 3). Results suggested that both α-amylase activity and protein significantly decrease the pasting viscosity of waxy rice flours. Chain length distribution of amylopectin as measured by high performance ion exchange chromatography (HPAEC-PAD) showed that starch with a higher ratio of short chain leads to a higher pasting viscosity. X-Ray diffractograms showed that the crystal type of all the four varieties of rice starches were characteristic A-type. Relative crystallinity of each rice starch was further calculated, and higher crystallization resulted in a higher viscosity. Our study would provide a fundamental knowledge of the relationship between different factors and waxy starch pasting properties, as well as be a reference for controlling the quality of waxy rice starch-based food products.